Reflections on narrow-reef platinum mining pillar design systems as applied to a large platinum exploration feasibility project - Zvarivadza, Tawanda; van der Merwe, J. N. (Journal of the Southern African Institute of Mining and Metallurgy, 2021)
Platinum is a highly valuable resource, its safe and economic extraction is paramount. The success of platinum mining by the bord and pillar method depends heavily on a comprehensive and dependable pillar design method. Pillars need to be large enough to safely support the load and small enough to avoid loss of resources. A critical evaluation of current pillar design systems used in narrow-reef platinum mining was undertaken using practical experience from a large feasibility-stage platinum exploration project, supplemented by observations from several platinum mines in Zimbabwe. An extensive literature survey was undertaken in order to determine the current status of design systems. Through this approach, the shortcomings of current pillar design systems are highlighted. Areas are proposed for further research to obtain a better understanding on how additional factors influence pillar system stability. The exploration work highlighted how rock mass classification methods can be utilized in determining the overall strength of pillars. Current pillar design systems for narrow-reef platinum mining consider width-to-height-ratio (usually with different exponents for width and height) and the strength of the pillar material. However, there are many more important factors that are not considered and which have a bearing on pillar system stability. An in-depth study of these parameters with a view to establish effective narrow- reef platinum mining pillar design systems needs to be undertaken.